O cardeal leme e a construção da ordem política católica (1930-1942) - Baldin, Marco Antonio [UNESP] (2014)
At the beginning of the twentieth century in Brazil, the configuration of Catholicism aimed to lend the Church a highly political character, so much so that the term Catholicism became synonymous with political struggle. Clashing with Christians, Catholics secularized the Church, engaging it in an action beyond the religious field, which is the main topic of this study. For the first time in the history of Brazil, Catholics were organized to fight for their political rights collectively. In Rio de Janeiro, Cardinal Sebastião Leme (1930-1942), which is the subject of the present work, had provided the Church with institutional support such as the Centro Dom Vital, in order to put the action of the Catholic community in the streets into practice. The Church would be a political actor, even though this hindered the intentions of its opponents, especially powerful men. Despite the fact it was not a political party, the Church was unofficially made up of political organs that directly interfered with the major decisions in the country, menacing the authority of influential people, who started fearing their leadership could be at risk and had to concede the Church a position of assistant to the secular government in the midst of the Republican Era This fear would originate the creation of the Pius Brazilian Pontifical College in Rome, Catholic cinemas, the Catholic Bank, welfare assistance funds, Catholic schools and several associations such as the Military Catholic Union and the Catholic Worker Circles. The Catholic practice and thought would arise with a solid framework and thus shape Catholic citizens, Catholic students, Catholic soldiers, Catholic lawyers, Catholic rights, Catholic workers, Catholic Brazilians. Despite the fact that the State did not become Catholic, its authoritarian vocation and indifference towards society became stronger, which explains the political trajectory of Brazil. Three chapters compose the present work: in...